Opportunities for sustainable, green and inclusive agricultural value chains in ACP countries - Westlake, M.J. (Technical Centre for Agricultural and Rural Cooperation, 2014)
The objective of this book, which summarises the findings of 18 value chains in 11 ACP countries, is to identify the factors affecting commercial value chain development. What factors help entrepreneurial initiatives and commercial viability? Which ones provide constraints? Aimed at governments, private companies, donors and NGOs, this detailed publication places emphasis on maximising the inclusion of smallholders. It also highlights some important green initiatives taken by the value chains studied. The text addresses concerns of efficiency and sustainability: the selected chains – which range from rubber processed in Cameroon to hot peppers grown in Jamaica, from sugarcane milled in Uganda to mangoes exported from Haiti and papaya grown on Fiji – all had to prove to be sustainable or to have the potential to be sustainable. Despite the great diversity of ACP agricultural value chains, a number of strong themes emerge. These include that: value chains established by a private initiative develop to exploit market opportunities; market liberalisation has a major impact; efficiency can be improved when small-scale farmers develop collaborative relationships with other value chain participants; and that the adoption of many green activities is driven by market forces.